Some Methods of Describing Echolocation Calls of Bats Using Cohen’S Class and Wavelet Algorithms - HERMAN, Krzysztof (Archives of Acoustics, 2008)
In this paper some digital signal processing algorithms, that are used for describing bats’echolocation calls of two different species of bats (Myotis daubentoni, Nyctulus noctula) arepresented. Analyzed algorithms are dedicated to calculate time frequency (TF) representationof digital signals. Spectrogram of the bat sonar call gives us information about many importantfeatures of the signal like type of frequency modulation which is one of the most importantsignal parameter. Comparative analysis of the algorithms mentioned in this paper suggeststhat we can select the best suitable method of analysis of bat’s sonar signals.